2016
DOI: 10.1080/13625187.2016.1263292
|View full text |Cite
|
Sign up to set email alerts
|

Folate, homocysteine and selected vitamins and minerals status in infertile women

Abstract: Folate levels were largely inadequate among women attending an infertility clinic for IVF. Vitamin B levels were also found to be inadequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…There was a beneficial effect of these combined antioxidants on embryo development [ 78 ], and a positive correlation between the presence of these antioxidants and increased blastocyst cells number [ 79 ]. The evidences about the efficacy of these compounds, administered alone in culture medium, in increasing the oocytes fertilization rate [ 93 , 94 ] and in improving embryo development [ 95 , 96 , 97 , 98 , 99 ] has also been highlighted in experimental studies [ 93 , 94 , 95 , 96 , 97 , 98 , 99 ].…”
Section: Agents Consideredmentioning
confidence: 99%
“…There was a beneficial effect of these combined antioxidants on embryo development [ 78 ], and a positive correlation between the presence of these antioxidants and increased blastocyst cells number [ 79 ]. The evidences about the efficacy of these compounds, administered alone in culture medium, in increasing the oocytes fertilization rate [ 93 , 94 ] and in improving embryo development [ 95 , 96 , 97 , 98 , 99 ] has also been highlighted in experimental studies [ 93 , 94 , 95 , 96 , 97 , 98 , 99 ].…”
Section: Agents Consideredmentioning
confidence: 99%
“…36,37 In infertile women attending an IVF clinic, it has been found that both RBC folate and vitamin B 12 levels were inadequate overall. 20 However, in those who used a folic acid supplement, there was a significantly greater likelihood of achieving the threshold for folate sufficiency (RBC folate > 906 nmol/L to protect against neural tube defects) 38 ; although few women in the folic acid group were replete (<30%), the proportion was nearly negligible in women who did not use any supplement. 20 In a study analyzing the levels of trace elements in women undergoing IVF, 39 serum and follicular fluid selenium and zinc, and follicular fluid copper levels, were significantly lower in IVF patients compared with controls.…”
Section: Supplementation With Micronutrients May Improve Fertilitymentioning
confidence: 99%
“…20 However, in those who used a folic acid supplement, there was a significantly greater likelihood of achieving the threshold for folate sufficiency (RBC folate > 906 nmol/L to protect against neural tube defects) 38 ; although few women in the folic acid group were replete (<30%), the proportion was nearly negligible in women who did not use any supplement. 20 In a study analyzing the levels of trace elements in women undergoing IVF, 39 serum and follicular fluid selenium and zinc, and follicular fluid copper levels, were significantly lower in IVF patients compared with controls. However, follicular fluid levels of aluminum and iron were significantly higher in IVF patients than in controls, which may reflect increased oxidative stress (known to enhance non-heme iron absorption).…”
Section: Supplementation With Micronutrients May Improve Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that Hcy concentration correlates with sperm, oocyte, and embryo qualities . Among 269 infertile women at a mean age of 37 ± 4 years, there were 69% presenting adequate plasma Hcy levels, and the pregnant women complicated with preeclampsia had significantly higher serum Hcy levels than healthy pregnant women at the same gestational age ( P < .001) . In addition, Hcy is reported to be inversely associated with fertility outcome, and lower Hcy levels have been found to correlate with a better chance of clinical pregnancy and better embryo grades in assisted reproductive technology (ART) .…”
Section: Introductionmentioning
confidence: 99%